Very rare near-haploid acute lymphoblastic leukemia resistant to immunotherapy and CAR-T therapy in 19-year-old male patient - Arpas, Tomas; Jelinkova, Hana; Hrabovsky, Stepan; Orsulova, Martina; Vrzalova, Zuzana; Navrkalova, Veronika; Brhelova, Eva; Bryjova, Lenka; Bulikova, Alena; Ondrouskova, Eva; Sejnohova, Marketa; Folber, Frantisek; et al. (Clinical case reports, 2022)
Near-haploid acute lymphoblastic leukemia is rare subgroup of the disease, which is very important due to very poor prognosis and resistance to treatment including novel monoclonal antibodies and CAR-T therapy.
Keywords: acute lymphoblastic leukemia; CAR‐T therapy; near‐haploid; inotuzumab ozogamicin; blinatumomab